2 0 1 1 + 2 0 1 1 2 − 1 1 = m − n where m and n are positive integers, what is value of m + n ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
how did u think it , huh ??
Let x = a + a 2 − 1 and y = a − a 2 − 1 . Then
x y = a + a 2 − 1 a − a 2 − 1 = a 2 − ( a 2 − 1 ) = 1 We want to express x − 1 = y as m − n for integers m and n . Note that ( x + y ) 2 = x 2 + 2 x y + y 2 = a + a 2 − 1 + 2 + a − a 2 − 1 = 2 a + 2 Thus x + y = 2 a + 2 . Similarly x − y = 2 a − 2 . So
y = 2 1 ( 2 a + 2 − 2 a − 2 ) = 4 2 a + 2 − 4 2 a − 2 = 2 a + 1 − 2 a − 1 = m − n The sum m + n = a . Therefore when a = 2 0 1 1 , the solution is 2 0 1 1 .
Let m = 2 x + 1 , n = 2 x − 1 . Then x − x 2 − 1 = m + n − 2 m n , so x + x 2 − 1 1 = m + n − 2 m n , and taking the square root of both sides gives us the desired result. In this case, x = 2 0 1 1 , m = 1 0 0 6 , n = 1 0 0 5 , m + n = x = 2 0 1 1 .
This demonstrates that the solution works; I got it by looking at the first equation and setting m + n = x and 4 m n = x 2 − 1 , and solving for m and n .
Problem Loading...
Note Loading...
Set Loading...
2 0 1 1 + 2 0 1 1 2 − 1 1 = 1 0 0 6 + 2 1 0 0 6 × 1 0 0 5 + 1 0 0 5 1
= ( 1 0 0 6 + 1 0 0 5 ) 2 1
= 1 0 0 6 + 1 0 0 5 1 = 1 0 0 6 − 1 0 0 5 1 0 0 6 − 1 0 0 5
= 1 0 0 6 − 1 0 0 5